2008
DOI: 10.1109/tcsvt.2008.927109
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Vision-Based Trajectory Learning and Analysis for Surveillance

Abstract: Abstract-This paper presents a survey of trajectory-based activity analysis for visual surveillance. It describes techniques that use trajectory data to define a general set of activities that are applicable to a wide range of scenes and environments. Events of interest are detected by building a generic topographical scene description from underlying motion structure as observed over time. The scene topology is automatically learned and is distinguished by points of interest and motion characterized by activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
229
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 421 publications
(231 citation statements)
references
References 90 publications
0
229
0
2
Order By: Relevance
“…Similar representations have previously been proposed by other authors and have shown to be useful for detecting trajectory anomalies [11,9]. Following Definition 1, let us formalise the concept of a sub-trajectory:…”
Section: Definition 1 a Trajectory Is A Continuos Parameterised Curvmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar representations have previously been proposed by other authors and have shown to be useful for detecting trajectory anomalies [11,9]. Following Definition 1, let us formalise the concept of a sub-trajectory:…”
Section: Definition 1 a Trajectory Is A Continuos Parameterised Curvmentioning
confidence: 99%
“…A large number of algorithms based on learning of normal trajectory patterns have been proposed for this problem [11]. However, these algorithms typically suffer from one or more of the following limitations: First, they are essentially designed for offline anomaly detection in databases, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are other works that successfully overcome the existent problems by building adaptive learning systems that can be applied to various scenes. Extensive surveys of related research that investigate and make use of trajectory information for video surveillance systems have been published [1][2][3].…”
Section: Related Workmentioning
confidence: 99%
“…An event is defined as the occurrence of a specific action performed by a subject in a particular place during a particular time frame [12]. Events are detected for the purpose of security for two key reasons [13][14][15]: warning of known threatening events [14,15] and searching for events of interest after the event has taken place.…”
Section: Related Workmentioning
confidence: 99%